The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/geo2.86
|View full text |Cite
|
Sign up to set email alerts
|

Planet of fixers? Mapping the middle grounds of independent and do‐it‐yourself information and communication technology maintenance and repair

Abstract: This paper explores the geographical distribution of independent and do‐it‐yourself information and communication technology maintenance and repair (INDIY ICT M&R) activity around the world. It examines a large set of Google Analytics data pertaining to users of free, open‐source online repair manuals provided by iFixit, a US‐based organisation that develops the free manuals, sells tools and components, and also engages in technical education and policy advocacy. The paper draws on three years of available use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…We further supplemented the more detailed information from Youtube repair videos by consulting repair guides for relevant models of smartphones and tablets available from iFixit. iFixit is a wiki-based site devoted to posting free repair instructions covering more than 13,000 devices in some dozen languages (Lepawsky, 2020). Combining information from the Youtube results and relevant iFixit manuals about specific repair steps, tools, intermediate materials, and components enabled us to add detail to our LCA analyses not otherwise available in existing LCA databases or literature (see the description of LCA later and Sections S1-S6 of Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…We further supplemented the more detailed information from Youtube repair videos by consulting repair guides for relevant models of smartphones and tablets available from iFixit. iFixit is a wiki-based site devoted to posting free repair instructions covering more than 13,000 devices in some dozen languages (Lepawsky, 2020). Combining information from the Youtube results and relevant iFixit manuals about specific repair steps, tools, intermediate materials, and components enabled us to add detail to our LCA analyses not otherwise available in existing LCA databases or literature (see the description of LCA later and Sections S1-S6 of Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…The mental aspects of repair are related to a new way of thinking to get away from overconsumption; they involve creativity and cultivating values such as care, upgrade, repurposing, and appreciation [5,8]. Researchers discuss the gender issues of repair, in which the technological aspects of repair are associated with males and care with females [33]. The researchers note that an important social function of repair is the development of local communities, solidarity through participation in repair cafes, and other events [28].…”
Section: Social Discoursementioning
confidence: 99%
“…Documenting ICT maintenance and repair at anything other than coarse scales of national or subnational regions is a challenge due to differing jurisdictional definitions of repair as an economic activity and what sectors of the economy are aggregated together to count that activity [24,47]. Using a novel dataset Lepawsky has recently demonstrated the global extent of independent and do-ityourself ICT maintenance and repair activity (INDIY ICT M&R) [22]. His results show that INDIY ICT M&R involves a growing population of people numbering in the millions of individuals who are ubiquitously, but unevenly, distributed around the world.…”
Section: Materials and Energy Conservation Potential Of Worldwide Indimentioning
confidence: 99%
“…First, although it has been shown that millions of people are engaged in INDIY ICT M&R activities around the world [22], it remains unclear whether sufficient scale is achieved to impart genuine material and energy savings. There is anecdotal evidence from Apple, the largest OEM by revenue, that third-party repair has slowed sales of iPhones, one of its flagship products [3].…”
Section: Materials and Energy Conservation Potential Of Worldwide Indimentioning
confidence: 99%